Bioanalysis during pregnancy: recent advances and novel sampling strategies. (December 2014) - Concheiro-Guisan, Ana; Concheiro, Marta
Consumption of drugs of abuse, tobacco and alcohol throughout pregnancy is a serious public health problem and results in an important economic cost to the health system. Drug and/or metabolites determination in biological matrices from mother and newborn is an objective measure of in utero drug exposure. We reviewed methods published for the determination of in utero drug exposure from 2007 to 2014, with special focus on meconium, placenta, umbilical cord and newborn hair. Accurate bioanalytical procedures are essential to obtain high-quality data to perform interventions and to establish correlations between analytical measures and clinical outcomes. We included a brief overview of clinical implications of in utero drug exposure to better understand the importance of this serious health issue.